The State of Sustainable Markets 2015 - International Trade Centre (United Nations, 2015)
This publication shows significant growth in sustainability markets. Offering a pathway to formalizing the reporting process, with a view to making data on sustainable markets more accessible to all, it provides a market data survey on Voluntary Sustainability Standards (VSS). The first section constitutes an overview of the VSS surveyed, including a short description and key data. Section two includes production-related data for key global sustainability standards across nine commodity sectors – bananas, cocoa, coffee, cotton, forestry, palm oil, soybeans, cane sugar and tea – and addresses each product's serious sustainability challenges, such as child labour, water scarcity, workers’ rights, use of chemicals, and more. Demonstrating ITC's support for